A study to assess the awareness of adults about precancerous and cancerous lesions and the associated risk factors - Arti Dixit; Nirav Hemant Parekh; Rakesh Anand; Nitesh Kamal; Bhumika K Badiyani; Amit Kumar; Vishnu Teja Obulareddy (Wolters Kluwer Medknow Publications, 2023)
Aim: The purpose of this study was to determine which factors contribute to the development of oral precancerous lesions and subsequent mouth cancer. Materials and Methods: Throughout the trial, 450 patients agreed to participate in the investigation. The subjects comprised patients with squamous cell carcinoma (n = 79), oral submucous fibrosis (OSF) (n = 200), leukoplakia (n = 41), lichen planus (n = 10), and controls (n = 120). Statistical analysis of the data was carried out using the Chi-square and regression analysis. Results: All oral precancerous lesions were shown to have a high prevalence of chewing, which was found to have a strong link with oral cancer. Oral precancerous lesions and cancer were also substantially connected with the length of time someone had the habit and how often they engaged in it. Conclusion: Oral cancer and precancerous lesions were determined to be less of a worry when other risks such as drinking and smoking were taken into account.